La imprescriptibilidad atípica de las pretensiones civiles ¿sólo la ley puede crear supuestos de imprescriptibilidad? - Varsi-Rospigliosi, Enrique (2022)
The authors question the premise that only the law can create cases of non-applicability of statutory limitations, since case law has also identified other cases of non-applicability of statutory limitations, beyond the typical cases expressly provided for in some articles of the Civil Code. This is a new study that, based on the doctrinal, jurisprudential and legal formant (national and comparative), seeks to describe each of the atypical assumptions of non-applicability and identify the reason for them.